Environmental factors affecting the development of knowledge management strategies in military organizations - Amir Niazmand; Hasan Zarei matin; Mohammad Rahmati (مطالعات مدیریت راهبردی, 2022)
Aim and Introduction: Advancement in the field of having a specialized workforce and advanced technologies in advancing the mission and improving the level of combat capability and improving their performance requires the use of knowledge management and the existence of a system in which organizational knowledge can be easily created, acquired and stored. Use the flow of various activities of military organizations. Accordingly, the Military organizations,  in order to advance its goals regarding knowledge management, needs a comprehensive, complete, practical and appropriate model in line with its strategic goals, which in this study intends to achieve this based on its vision and mission. Therefore, the present article seeks to explain the environmental factors affecting the development of knowledge management strategies of military organizations.Methodology: This research is based on the type of applied research, and in terms of its nature and method, based on the descriptive research method, it conforms to the approach of mixed data analysis (qualitative-quantitative).The statistical population of this research includes 245 commanders, deputies, deputies, managers. The experts, experts, veterans, researchers and strategic working groups of knowledge management are the subordinate units of the Iranian Armed Forces, and 150 people were selected as a sample using Cochran's formula. In this research, library method (documents and documents) and field method (interview and questionnaire) were used to collect data. Qualitative data analysis was done using content analysis method (grounded data theorizing) and quantitative data analysis was done through SWOT and TOPSIS using SPSS statistical software. Cronbach's alpha coefficient was also used for the reliability of the questionnaire.Findings: The findings of the research show that there are a total of 132 indicators that have the greatest impact on the development of knowledge management strategies in military organizations, which include 95 indicators regarding internal environment factors (29 indicators regarding the component the strengths of knowledge management and 66 indicators regarding the component of knowledge management weaknesses) and 37 indicators regarding external environment factors (20 indicators regarding the component of knowledge management opportunities and 66 indicators regarding the component of threats of knowledge management).Discussion and Conclusion: By calculating the average of internal and external factors and according to the sum of the calculated weighted points, about %75 of the people in the sample society (the relative majority) rated the status of the factors of the internal environment effective on the knowledge management of the Iranian Armed Forces as medium to low. And about %58 of the people in the sample community (relative majority) know the status of the current situation of the factors of the external environment effective on the knowledge management of the medium to high level, and it shows a significant opportunity in this dimension.After compiling the matrix of strengths, weaknesses, threats and opportunities of knowledge management in the Iranian Armed Forces (SWOT) and comparing two by two factors related to internal and external variables, 16 final strategies resulting from the improved SWOT matrix They have been counted in a survey of experts. Finally, TOPSIS method has been used to prioritize knowledge management strategies in military organizations (J.A. Iran Army) and to examine the effectiveness of extraction strategies.